PROGRESSIVE STEPS FOR PREVENTING AND HANDLING MONEY POLITICS IN INDONESIAN ELECTIONS: AN EFFORT TO REDUCE DEVIANT BEHAVIOR IN DEMOCRATIC ELECTIONS - Djufri, Darmadi (Universitas Lampung, 2023)
The practice of money politics in election process is primarily observed during campaign activities and distribution of donations, specifically cash contributions. This occurrence can be attributed to several factors, namely tradition, desire for recognition, conducive environment, the ability to influence laws, wavering ethical values, impoverished communities, limited public awareness, and culture. Furthermore, money politics is primarily conducted in two stages, namely pre-voting and post-voting. The pre-voting phase comprises administrative selection, the campaign period, quiet period, and the lead-up to the actual election. The targets are primarily voters susceptible to influence, while the post-election phase occurs after the election, specifically during the General Session of the DPR/DPRD and when making decisions about the APBN/APBD. The targets are mainly political elites who hold the sovereignty of the people and possess the authority to make strategic decisions. Considering the existence of legal loopholes that can be exploited by various parties for fraudulent purposes, specifically money politics, it is imperative to enhance the clarity of existing legal provisions. In addition, perpetrators often exploit these loopholes, necessitating more robust legal measures.